FORMATION OF GENDER CULTURE AMONG EDUCATIONAL STAFF (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article presents foreign experience in the formation of gender culture among teaching staff of higher educational institutions. At the same time, it is necessary to develop effective mechanisms for introducing gender culture into the education system and managing it. Information is provided on the relevance of considering the problems of forming gender culture among teachers and implementing measures to form them.